Assessment of Overtourism Manifestations by Visitors of Russian Destinations. The Case from Sochi - VETITNEV, Alexander Mikhailovich; CHIGAREV, Dmitriy Valerievich (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021DO - 10.14505/jemt.12.1(49).19, 2021)
The article continues the study of the reasons influencing the risk of overtourism-related challenges in Sochi resort. Some elements of influence of the area overcrowding as the main manifestation of overtourism on the visitors have been studied. The relationship between various aspects of the visitors' perception of people congestion in the resort city has been considered. Attention has been paid to such most informative factors as socio-demographic and behavioral characteristics of the visitors and the existence of conflicts between holidaymakers and the locals. The reasons that annoy tourists during their stay in Sochi have been analyzed. Based on the fact of a relatively small number of conflicts between tourists and locals, as well as a fairly high overall satisfaction of the visitors, it may be concluded that there is no unconditional impact of overtourism on the quality of the experience of the visitors to the Sochi resort. Identification of the factors of overcrowding influence on tourists satisfaction and loyalty and expanding the visitor experience monitoring toolkit can be useful as well for managing tourism development in well-developed tourism destinations.